Toward clean suspended CVD graphene. Issue 87 (5th September 2016) - Yulaev, Alexander; Cheng, Guangjun; Hight Walker, Angela R.; Vlassiouk, Ivan V.; Myers, Alline; Leite, Marina S.; Kolmakov, Andrei
Abstract : Anthracene was proposed as a new easily evaporable sacrificial layer for a dry CVD graphene transfer. Abstract : The application of suspended graphene as electron transparent supporting media in electron microscopy, vacuum electronics, and micromechanical devices requires the least destructive and maximally clean transfer from their original growth substrate to the target of interest. Here, we use thermally evaporated anthracene films as the sacrificial layer for graphene transfer onto an arbitrary substrate. We show that clean suspended graphene can be achieved via desorbing the anthracene layer at temperatures in the 100 °C to 150 °C range, followed by two sequential annealing steps for the final cleaning, using a Pt catalyst and activated carbon. The cleanliness of the suspended graphene membranes was analyzed employing the high surface sensitivity of low energy scanning electron microscopy and X-ray photoelectron spectroscopy. A quantitative comparison with two other commonly used transfer methods revealed the superiority of the anthracene approach to obtain a larger area of clean, suspended CVD graphene. Our graphene transfer method based on anthracene paves the way for integrating cleaner graphene in various types of complex devices, including the ones that are heat and humidity sensitive.